The Quarterly Journal of Economics Volume 131 May 2016 Issue 2 - Front Cover (Quarterly Journal of Economics, 2016)
Journal Article The Quarterly Journal of Economics Volume 131 May 2016 Issue 2 - Front Cover Get access The Quarterly Journal of Economics, Volume 131, Issue 2, May 2016, Page i1, https://doi.org/10.1093/qje/qjv048 Published: 19 May 2016